Criminal Liability of a Juvenile Offender in Sexual Violence Resulting in Reproductive Organ Injury to the Victim - Berliansari, Novia Safitri; Kantikha, I Made; Markoni; Sembiring, Malemna Sura Anabertha (GoAcademica Research & Publishing, 2026)
This study examines juvenile criminal liability and judicial reasoning in Decision No. 12/Pid.Sus-Anak/2025/PN Sbw through the lens of proportional justice. Employing normative (doctrinal) legal research, the study applies statutory, conceptual, and case approaches by analyzing the applicable legal framework on juvenile justice and sexual violence, relevant criminal law doctrines on liability and causation, and the structure of the court’s reasoning. The findings show that the elements of criminal liability were established covering the actus reus, mens rea, accountability, and the causal nexus between the conduct and the victim’s injury, and yet the sentencing rationale largely centered on the offender’s status as a child under the Juvenile Criminal Justice System Act. As a result, the judgment did not sufficiently articulate the victim’s severe reproductive harm as a decisive aggravating factor for proportional sentencing. This study argues for more robust and transparent judicial reasoning that integrates juvenile justice principles with victim-protection mandates, including a harmonized reading of the juvenile justice regime and the sexual violence legal framework, to secure a substantively fair balance between child protection and victims’ rights.